Cellulose acetate ultrafiltration membranes customized with copper oxide nanoparticles for efficient separation with antifouling behavior. Issue 8 (2nd October 2020) - Vetrivel, Selvaraj; Saraswathi, Meenakshi Sundaram Sri Abirami; Rana, Dipak; Divya, Kumar; Nagendran, Alagumalai
Abstract: Cellulose acetate (CA) nanocomposite ultrafiltration membranes are fabricated with copper oxide (CuO) nanoparticles with the aim of improving efficient protein separation and antifouling performance. CuO nanoparticles are synthesized from cupric nitrate using a wet precipitation method and characterized by FTIR and XRD. CA/CuO nanocomposite membranes fabricated using 0.5, 1.0, and 1.5 wt% of CuO nanoparticles individually by simple phase inversion technique. The CA nanocomposite membrane with 0.5 wt% of hydrophilic CuO exhibited enhanced PWF of 118.6 Lm −2  h −1 due to the improvement in porosity and water uptake. This is in good agreement with the enhanced hydrophilicity of the CA/CuO nanocomposite membranes results observed in surface contact angle and morphological investigations. Further, 95.5% of BSA separation and 94.7% of flux recovery ratio (FRR) indicates its superior antifouling potential caused due to the presence of the hydration layer at the CA/CuO membrane surface. Among all the fabricated membranes, the CA‐0.5 nanocomposite membrane with 0.5 wt% of CuO exhibited superiorly improved hydrophilicity, water permeation, BSA separation, and antifouling performance indicates its potential use in water and wastewater treatment applications. Abstract : Highly permeable and antifouling CA/CuO nanocomposite ultrafiltration membranes.